To buy or to borrow? Evaluating the cost of an eBook in TalTech library. Issue 1 (20th January 2020) - Kont, Kate-Riin
Abstract : Purpose: The purpose of this paper is to find out how much the purchasing and lending of individual electronic books really cost. Additionally, this paper investigates which kind of approach would be cheaper and less time-consuming for library staff as well as library patrons – purchase or short-term loan. Design/methodology/approach: This study was conducted at the Tallinn University of Technology (TalTech) Library. This is the only university library in Estonia where the Ebook Central platform is adapted on a large scale. For background information, all statistical data of expenditures and average prices of purchases and short-term loans during April 2013 and December 2018 were calculated and analysed. Through a case study, the time-driven activity-based costing (TDABC) method was used – all activities related to acquisition and lending of eBooks were identified, recorded in detail and analysed. More specifically, the study concerned eBooks offered in the Ebook Central platform and covered purchasing and short-term loan processes, such as receipt of order request, communication with the patron (if necessary) making a purchase or short-term loan, and feedback to the patron. Findings: While analysing the results, it appeared there are many additional activities libraries can avoid during the eBook short-term loan process compared to purchasing. As a normality in TalTech library, purchase is always followed by a cataloguing process which increases the time and cost of this process in turn. On the basis of the current study, it can be said that short-term loan is a cheaper way to use eBooks; many activities related to the short-term loan of eBooks take remarkably less staff time and financial resources than eBooks acquisition/purchasing activities. When analysing the literature reviewed as well as collected statistical data, the problem may arise when the decision-maker librarian is not experienced, professional or long-sighted enough to understand the future behaviour of the patron or the usage of the specific eBook. When the usage reaches a certain point, it becomes an indicator of continuing future usage and so it makes sense to purchase the eBook, as the library pays no further charges once an eBook is owned. Originality/value: Most studies reviewed by the author are based on the statistical data collected about expenditure, costs, usage, cost-per-use, etc. of short-term loans and purchases. While acquisitions costs, average cost per acquired item per year and cost per usage are easy to identify, it has been difficult to measure associated costs of acquisition, cataloging and circulation. The TDABC methodology seems to be one of the best tools for understanding cost behaviour and refining a cost system for university libraries. Based on the information known to the author, there is no study carried out using the TDABC methodology for analysing costs of eBook programmes.